UJI EFEK ANALGESIK EKSTRAK ETANOL UMBI BAWANG DAYAK (Eleutherine americana L. Merr) PADA MENCIT JANTAN (Mus musculus) - admin; Taufiq Taufiq (Akademi Farmasi Yamasi Makassar, 2022)
This study was conducted to determine the analgesic effect of the ethanolic extract of Dayak onion bulbs (Eleutherinr americana L. Merr) on male mice (Mus musculus). 15 adult male mice were used which were divided into 5 groups and each group consisted of 3 animals with stretching observation time from 5 minutes to 60 minutes. Group I was given 1% Na CMC as a negative control, group II, III, and IV were given ethanol extract of Dayak Onion Bulbs with extract doses of 1.17 mg/0.5 ml, 2.34 mg/0.5 ml, and 4.68 mg/0.5 ml with a volume of 1 ml /30-gram BW orally with a volume of 1 ml/30 g body weight of mice. The results of the study on the administration of Dayak onion bulb extract (Eleutherine americana L. Merr) with extract doses of 1.17 mg/0.5 ml, 2.34 mg/0.5 ml, and 4.68 mg/0.5 ml, respectively. -the average percentage of stretching (19.48 %), (36.02 %), (62.11% %), while the administration of mefenamic acid suspension was 1.3 g/0.5 ml, the percentage of stretching was (76 ,48 %). Statistical test using SPSS 25 with the one way ANOVA method on the LSD follow-up test to see whether there is a difference in the analgesic effect of the extract shows a significant value of 0.000 (p < 0.005), which means that there is a significant difference between treatments (significant), at a confidence level of 5 % (Î± = 0.05).